2011
DOI: 10.1111/j.1365-313x.2011.04575.x
|View full text |Cite
|
Sign up to set email alerts
|

The basic helix‐loop‐helix transcription factor CrMYC2 controls the jasmonate‐responsive expression of the ORCA genes that regulate alkaloid biosynthesis in Catharanthus roseus

Abstract: SUMMARYJasmonates are plant signalling molecules that play key roles in defence against insects and certain pathogens, among others by controlling the biosynthesis of protective secondary metabolites. In Catharanthus roseus, the AP2/ERF-domain transcription factor ORCA3 controls the jasmonate-responsive expression of several genes encoding enzymes involved in terpenoid indole alkaloid biosynthesis. ORCA3 gene expression is itself induced by jasmonate. The ORCA3 promoter contains an autonomous jasmonate-respons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
247
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 303 publications
(253 citation statements)
references
References 39 publications
5
247
1
Order By: Relevance
“…The repression of ORF by CrWRKY1-SRDX derepresses the ORCA3 promoter, leading to the up-regulation of ORCA3. Alternatively, CrWRKY1 regulates ORCA3 by repressing CrMYC2, which controls the JA-responsive expression of ORCA3 (Zhang et al, 2011). Our results are in agreement with recent observations showing that JA induction increases TIA accumulation in C. roseus hairy roots, yet, overexpression of ORCA3 does not enhance TIA production (Peebles et al, 2009).…”
Section: Overexpression or Repression Of Crwrky1 Affects The Accumulasupporting
confidence: 83%
See 1 more Smart Citation
“…The repression of ORF by CrWRKY1-SRDX derepresses the ORCA3 promoter, leading to the up-regulation of ORCA3. Alternatively, CrWRKY1 regulates ORCA3 by repressing CrMYC2, which controls the JA-responsive expression of ORCA3 (Zhang et al, 2011). Our results are in agreement with recent observations showing that JA induction increases TIA accumulation in C. roseus hairy roots, yet, overexpression of ORCA3 does not enhance TIA production (Peebles et al, 2009).…”
Section: Overexpression or Repression Of Crwrky1 Affects The Accumulasupporting
confidence: 83%
“…TIA biosynthesis responds strongly to a group of chemical or fungal elicitors that are known to regulate gene transcription, providing an explanation for why the manipulation of TFs often results in substantial effects to the TIA pathway (El-Sayed and Verpoorte, 2007). Promoter analyses of several structural and TF genes related to the C. roseus TIA pathway have revealed the presence of chemical-and elicitorresponsive cis-elements, leading to the cloning of jasmonate-responsive TFs including the AP2-like ORCA2 and ORCA3 (Menke et al, 1999;Ouwerkerk and Memelink, 1999;, the G box-binding factors CrGBF1 and CrGBF2 (Sibéril et al, 2001), the P box-binding factor CrBPF1 (van der , the zinc-finger repressors ZCT1 (for zinc-finger C. roseus transcription factor 1), ZCT2, and ZCT3 (Pauw et al, 2004), and the basic helix-loop-helix TF CrMYC2 (Zhang et al, 2011).…”
mentioning
confidence: 99%
“…This complexity undoubtedly requires an array of TFs (1), many of which remain to be discovered. The expression of several of these TFs may be JA inducible as part of the JA signaling cascade, as previously shown for ORCA3 and MYC2 (13,15). This feature has turned out to be a powerful tool in the past to find pathway-regulating TFs in different plant species (1,4,35) and has been also successfully exploited here to identify the TF BIS1 as a regulator of the iridoid pathway.…”
Section: Discussionmentioning
confidence: 55%
“…The phytohormone jasmonate is a key elicitor of specialized metabolism (Aerts et al, 1994;Singh et al, 1998;Qi et al, 2011;Lenka et al, 2012), primarily through the induction of key TFs, such as MYC2 and ethylene response factors, that regulate the biosynthetic genes (van der Fits and Memelink, 2000;Shoji et al, 2010;Shoji and Hashimoto, 2011;Zhang et al, 2011;Patra et al, 2013;Schweizer et al, 2013;Sears et al, 2014). Study of the grape (Vitis vinifera) WRKY family found that 80% of WRKY genes are jasmonate responsive .…”
Section: The Present: Wrky Tfs As Key Regulators Of Specialized Metabmentioning
confidence: 99%